Bioelectricity generation using microalgal biomass as electron donor in a bio-anode microbial fuel cell. (December 2018) - Ndayisenga, Fabrice; Yu, Zhisen; Yu, Yang; Lay, Chyi-How; Zhou, Dandan
Graphical abstract: Highlights: C. regularis biomass was a promising MFC anolyte, with 0.43 g/g-DW BOD. The algae-fed MFC produced power densities close to that of the acetate-fed. COD removal of the algae-fed MFC reached 65.2%, slightly lower than the acetate-fed. The algae-fed MFC enriched a more diverse anode respiring bacteria community. The algae-fed MFC possessed greater Shannon index (4.27) vs. the acetate-fed (3.09). Abstract: In this study, microalgal biomass waste ( Chlorella regularis ) was treated while simultaneously producing bioelectricity in a microbial fuel cell (MFC). Algal biomass was the sole electron donor and was enriched with easily biodegradable proteins (46%) and carbohydrates (22%). The generated power density was 0.86 W/m 2 and the columbic efficiency reached ∼61.5%.The power generation could be further increased to 1.07 W/m 2 by using a biomass waste concentration enhancement strategy with maximum chemical oxygen demand (COD) removal of ∼65.2%. Via direct comparison, the power generation and COD removal capability of the algal-fed MFC was close to that of the commercial acetate-fed MFC. The algae-fed MFC presented superior electrochemical characteristics that were attributed to the complicated composition of the biomass anolyte. It possessed a multiple anode respiring bacterial group and diverse microbial community. Hence, this study provides a new strategy for the utilization of microalgal biomass as a bioresource.